1977
DOI: 10.2478/cttr-2013-0427
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Fatty Compounds and Surfactants Used as Sucker Control Agents on Field Tobacco

Abstract: The fate of fatty compounds and surfactants used for tobacco sucker inhibition was studied with 14C-labelled materials applied to field-grown Nicotiana tabacum L. cv. Maryland Catterton plants. Residual materials recovered from test tobacco showed the following: [ 1 ] When lauric acid was used, the residual material was maintained essentially in the acid fraction. [2] When lauryI alcohol was used, a considerable part (9.7-24.8 %) was converted to the acid fraction, indicating possible oxidation of alcohol in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…These levels may reflect the residues of either the mixed-function derivatives or the free polyoxyethylene, depending on whether the label was on the fatty-acid moiety or on ethylene oxide. Further studies by Tso and Chu (8) showed that most of the residue from Tween 80 applied on field-grown tobacco was hydrolyzed to free polyols and fatty acids. The study reported here was undertaken to monitor polyoxyethylene[20]sorbitan monooleate (Tween 80) residues remaining on green and cured tobacco leaf treated with a sucker-control agent formulated with this surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…These levels may reflect the residues of either the mixed-function derivatives or the free polyoxyethylene, depending on whether the label was on the fatty-acid moiety or on ethylene oxide. Further studies by Tso and Chu (8) showed that most of the residue from Tween 80 applied on field-grown tobacco was hydrolyzed to free polyols and fatty acids. The study reported here was undertaken to monitor polyoxyethylene[20]sorbitan monooleate (Tween 80) residues remaining on green and cured tobacco leaf treated with a sucker-control agent formulated with this surfactant.…”
Section: Introductionmentioning
confidence: 99%